Public procurement and reputation: An agent-based model - Nadia Fiorino; Emma Galli; Ilde Rizzo; Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
Based on the literature on public procurement regulation, we use an Agent-Based Model to assess the performance of different selection procedures. Specifically, we aim at investigating whether and how the inclusion of reputation of firms in the public procurement selection process affects the final cost of the contract. The model defines two types of actors: i) firms potentially competing to win the contract; ii) a contracting authority, aiming at minimizing procurement costs. These actors respond to environmental conditions affecting the actual costs of carrying on the project and unknown to firms at the time of bidding and to the contracting authority. The results from the model are generated through simulations by considering different congurations and varying some parameters of the model, such as the firms' skills, the level of opportunistic rebate, the relative weight of reputation and rebate. The main conclusion is that reputation matters and some policy implications are drawn.
Keywords: H57; L14; 330; R&D; Public works; Procurement; Agent-based modelling